Pengaruh Kepercayaan Konsumen Terhadap Keputusan Pembelian Secara Online - Agus Sobandi; Bambang Somantri (Institut Manajemen Wiyata Indonesia, 2020)
Trust is the main capital for the success of online buying and selling transactions because buyers have limitations to directly reach the physical conditions of the goods being traded and cannot meet face to face with the seller directly. This research was conducted to dig deeper and present empirical data, whether consumer trust affects online purchasing decisions. The research method used in this research is quantitative, by conducting explanatory research to determine the causal relationship between the variables studied. Data collection was carried out by survey techniques through a research instrument in the form of a questionnaire and addressed to 100 UMMI student respondents. Testing the quality of the instrument was carried out through validity and reliability tests. Hypothesis testing is done using regression analysis test tools. The test results show that consumer trust has a positive and significant effect on students' online purchasing decisions. The dimension of integrity underlies respondents' trust in e-commerce transactions or online buying and selling.